Segmental Financial Disclosure by Diversified Firms and Security Prices: A Reply. - Kochanek, Richard F. (The Accounting Review, 1975)
In this article, the author presents a reply to the criticism of his paper "Segmental Financial Disclosure by Diversified Firms and Security Prices," published in the April 1974 issue of the journal "The Accounting Review." Researchers R.M. Barefield and E.E. Comiskey, attempt to expand upon the author's paper by employing a "more direct" measure of earnings forecast performance and through introducing additional experimental controls into the analysis. The intent of the paper was to examine the effects of segmental disclosure in the annual financial reports of a selected sample of diversified firms on earnings predictability and stock price variability. Barefield and Comiskey propose that a computation of mean absolute percentage forecast errors based on a comparison of actual earnings and forecasts of earnings taken from the Earnings Forecaster service of Standard and Poor's Corp. constitutes a "more direct" and, therefore, more desirable approach to the problem. The author has attempted to emphasize the importance of weighing the benefits of alternative data sources and selecting the most appropriate comparative time periods.